The Pros and Cons of a Field Project: The case of the Laboratory School in Heredia - Dobles Trejos, Cecilia (2010)
This article reviews some of the most important characteristics of the Laboratory School in Heredia, Costa Rica, for recognizing the success aspects and setbacks that an innovative experience of an educational project has within the national education system. It is a description of the pedagogical model of the school and includes the vision that different participants have in this educational project, around which it is showed the different positions of the actors who live and reflect daily in the school.